Decreased Penetration Mechanism of Ranitidine Due to Application of Sodium Sulfobutyl Ether-β-Cyclodextrin - Rui Yang; Jing Zhang; Jiaqi Huang; Xiaofeng Wang; Huiying Yang; Qingri Jin (MDPI AG, 2023)
Permeability has an important effect on drug absorption. In this study, the effect of different concentrations of sodium sulfobutyl ether-β-cyclodextrin (SBE-β-CD) on the absorption of ranitidine was investigated to examine the mechanism of permeability changes. The results of a parallel artificial membrane permeability assay (PAMPA) showed that increasing the concentration of sodium sulfobutyl ether-β-cyclodextrin, 0, 0.12% (w/v), 0.36% (w/v) and 3.6% (w/v), respectively, caused the apparent permeability coefficient of ranitidine to decrease to 4.62 × 10−5, 4.5 × 10−5, 3.61 × 10−5 and 1.08 × 10−5 in Caco-2 cells, respectively. The same results were obtained from an oral pharmacokinetic study in rats. Further studies indicated that SBE-β-CD significantly increased the zeta potential of ranitidine. SBE-β-CD interacted with ranitidine charges to form a complex that reduced ranitidine permeability, and SBE-β-CD should be chosen with caution for drugs with poor permeability.